High Resolution View on the Regulation of Recombinase Accumulation in Mammalian Meiosis - Mhaskar, Aditya N.; Koornneef, Lieke; Zelensky, Alex N.; Houtsmuller, Adriaan B.; Baarends, Willy M. (Frontiers in Cell and Developmental Biology, 2021)
A distinguishing feature of meiotic DNA double-strand breaks (DSBs), compared to DSBs in somatic cells, is the fact that they are induced in a programmed and specifically orchestrated manner, that includes chromatin remodeling prior to DSB induction. In addition, the meiotic homologous recombination (HR) repair process that follows, is different from HR repair of accidental DSBs in somatic cells. For instance, meiotic HR involves preferred use of the homolog instead of the sister chromatid as a repair template and subsequent formation of crossovers and non-crossovers in a tightly regulated manner. An important outcome of this distinct repair pathway is the pairing of homologous chromosomes. Central to the initial steps in homology recognition during meiotic HR is the cooperation between the strand exchange proteins (recombinases) RAD51 and its meiosis-specific paralog DMC1. Despite our understanding of their enzymatic activity, details on the regulation of their assembly and subsequent molecular organization at meiotic DSBs in mammals have remained largely enigmatic. In this review, we summarize recent mouse data on recombinase regulation via meiosis-specific factors. Also, we reflect on bulk “omics” studies of initial meiotic DSB processing, compare these with studies using super-resolution microscopy in single cells, at single DSB sites, and explore the implications of these findings for our understanding of the molecular mechanisms underlying meiotic HR regulation.